PROFILE CONCEPTUAL UNDERSTANDING OF SECONDARY SCHOOL STUDENTS ASSOCIATED WITH CONCEPTUAL CHANGE REGARDING MATERIAL CHANGES - Hutnal Basori; Andi Suhandi; Ida Kaniawati; Dadi Rusdiana (Jurnal Pengajaran MIPA, 2019)
This study was conducted to determine the model of student’ understandings of changes in the states of matter. An conceptual understanding test  related to the concepts on the changes in the states of matter subject matter  atau disingkat  CSMCUtest  was constructed and given to 40 high school students. Each test item consists of four parts of questions, namely questions A to D. Questions A to C asking students to explain a case determine the physics law related to the case and write a case suitable for the related law or concept. Whereas question D asking students to define concepts of melting, evaporation, condenses and deposition.The data analysis was carried out to determine the quantity of high school students in each category of understanding model,  that  is:  Optimum Model (OM), Uncreative Model (UM), Theoretical Model (TM), Practical Model (PM), Memorizing Model (MM) and Inappropriate Model (IM). As a result of the data analysis it was determined that only a few students had a optimum understanding model. The results showed that the high school student’ have significant weaknesses in understanding the terms of fundamental knowledge of  changes in the states of matter. This may stem from the lack of student to relate scientific knowledge with real life phenomena and experiences.